Social support, depression, and heart disease: a ten year literature review - Compare, Angelo; Zarbo, Cristina; Manzoni, Gian Mauro; Castelnuovo, Gianluca; Baldassari, Elena; Bonardi, Alberto; Callus, Edward; Romagnoni, Claudia (Frontiers in Psychology, 2013)
Background: Coronary heart disease is the major cause of morbidity and mortality in the world. Psychosocial factors such as depression and low social support are established risk factors for poor prognosis in patients with heart disease. However, little is known about the hypothetical relationship pattern between them. Purpose: The purposes of this narrative review are (1) to appraise the 2002-2012 empirical evidence about the multivariate relationship between depression, social support and health outcomes in patients with heart disease; (2) to evaluate the methodological quality of included studies. Method: PubMed and PsychINFO were searched for quantitative studies assessing the multiple effects of low social support and depression on prognosis outcomes in patients with heart disease. The following search terms were used: social relation*, cardiac disease, support quality, relationship and relational support. Results: Five studies (3 prospective cohort studies, 1 case-control study and 1 randomization controlled trial) were selected and coded according to the types of support (social and marital). The majority of findings suggests that low social support/being unmarried and depression are independent risk factors for poor cardiac prognosis. However, all analyzed studies have some limitations. The majority of them did not focus on the quality of marital or social relationships, but assessed only the presence of marital status or social relationship. Moreover, some of them present methodological limitations. Conclusion: Depressive symptoms and the absence of social or marital support are significant risk factors for poor prognosis in cardiac patients and some evidence supports their independence in predicting adverse outcomes. Cardiac rehabilitation and prevention programs should thus include not only the assessment and treatment of depression but also a specific component on the family and social contexts of patients.